Directions for improving the regulation of the innovation circulation in the European Union through the prism of the implementation of the European Innovation Act (EIA) - Davydiuk, Oleksandr; Shovkoplias, Hanna; Borysov, Igor; Holina, Olena; Sokolova, Irina (Technology audit and production reserves, 2025)
The object of the research is the system of measures and methods of regulatory influence on the processes of innovation circulation in the European Union, through the prism of the prospective agreement EUROPEAN INNOVATION ACT (EIA). The current methods of identifying innovation circulation in the EU are studied, as well as the prospects for development within the framework of the implementation of EIA. The research found that the process of regulating innovation circulation in the EU is not unified. It is proven that the existing regulatory model of state influence in the EU is not focused on simplifying and stimulating its circulation. The main task is to intensify and scale the number of innovations within the EU economic system. It was determined that within the EU there is a need to improve the regulatory approach to determining the rules for the functioning of innovation circulation in the EU. A study of the areas of regulatory influence within the framework of the prospective EUROPEAN INNOVATION ACT was conducted. The results of a public discussion of its possible content were analyzed. Proposals were formulated for making changes to its text. The need to introduce a single definition of innovation, the formation of a preferential tax regime, is substantiated. The need to change the object of regulation and its focus on the system of economic relations Innovation Life Cycle is proven. The research is aimed at formulating proposals for improving the regulatory processes of innovation circulation in the EU. The results of this research can be used to improve the official rules of innovation circulation in the EU, as well as at the level of national systems of EU member states. They can also be used to form strategic public management decisions, state policy on innovation circulation, and they can serve as the basis for further scientific research on these issues.